The role of Islamic spirituality in the management and leadership process - Mahazan, Abdul Mutalib, 1981-; Rafiki, Ahmad, 1981- (Advances in logistics, operations, and management science (ALOMS) book series., 2021)
"This book elaborates on the spirituality and Qalb in human life and discusses the necessity that the leaders have to understand the role and function of Qalb in the leadership process"--